[Cranfield DrivAer] CAD_Pack_7 Spoilers - Francisco Soares, Renan; Golons Olives, Sergio; Garry, Kevin; Holt, Jenny (Cranfield University, 2018)
Spoilers CAD Pack (35% scaled-version), including:1. DrivAer_hp - Spoiler (spL040 spA40): Spoiler pack with plate size of 40 mm, set at 40 deg.2. DrivAer_hp - Spoiler (spL080 spA40):Spoiler pack with plate size of 80 mm, set at 40 deg.3. DrivAer_hp - Spoiler (spL120 spA40):Spoiler pack with plate size of 120 mm, set at 40 deg.4. DrivAer_hp - Spoiler (spL080 spA20):Spoiler pack with plate size of 80 mm, set at 20 deg.5. DrivAer_hp - Spoiler (spL080 spA60):Spoiler pack with plate size of 80 mm, set at 60 deg.CAD files available in IGS, STEP, STL, and Parasolid formats. All geometries are provided in [mm].Notation:(spL) = length of the spoiler plate.(spA) = angle of the spoiler plate, in reference to the ground. CAD designed and uploaded by:Renan F Soares - PhD in AerospaceApplied Aerodynamics GroupCranfield University, United Kingdom
Keywords: CAD'; 'DrivAer'; 'Automotive'; 'Aerodynamics'; 'Spoiler'; 'Aerodynamics (excl. Hypersonic Aerodynamics)'; 'Automotive Engineering not elsewhere classified'